2023
DOI: 10.3390/children10061044
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Child and Father–Child Emotional Availability during the COVID-19 Pandemic

Maggie Dungan,
Michael Lincoln,
Stephen Aichele
et al.

Abstract: While the body of literature on COVID-19’s impacts on family life is rapidly expanding, most studies are based entirely on self-report data, leaving a critical gap in observational studies of parent–child interactions. The goal of this study was to evaluate parent–child relationships during the COVID-19 pandemic using the observational emotional availability (EA) construct. Parents (n = 43) were assessed using the Epidemic–Pandemic Impacts Inventory (EPII), the Flourishing Scale (FLS), and the adverse childhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…There were no significant differences in emotional availability between the pre-and post-lockdown group. While most mentioned studies found alterations of emotional availability during the pandemic [28,29,31], Shakiba et al [33] report that EA-scores are consistent before and during the pandemic in a study with infants. This is in line with our findings.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There were no significant differences in emotional availability between the pre-and post-lockdown group. While most mentioned studies found alterations of emotional availability during the pandemic [28,29,31], Shakiba et al [33] report that EA-scores are consistent before and during the pandemic in a study with infants. This is in line with our findings.…”
Section: Discussionmentioning
confidence: 97%
“…This effect is not visible in mother-infant-dyads recruited after the onset of the first German lockdown-though the direct comparison of this correlation did not reveal any effect. Arguably, the new conditions evoked by the pandemic, with their rising levels of maternal fear and an unexplainable outside world, could have led to differences in the interaction [28,32]. While no differences in the levels of emotional availability were observed, the outcome might differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation